Auditor's Independence and Experience on Inspectorate Quality with Auditor's Professional Ethics as a Moderation Variable - Ni Kadek Dwi TRISNAYANTI; I Made Wianto PUTRA; I Dewa Ayu KRISTIANTARI (PT. Keberlanjutan Strategis Indonesia, 2023)
Purpose:This research empirically tests the influence of auditor independence and experience on the audit quality of the Badung Regency Government Inspectorate with auditor professional ethics as a moderating variable.Methodology:The type of data used in this research is quantitative data. The 36 samples used in this research were obtained using non-probability sampling with the Saturated Sampling method. The primary data source in this research is obtained by distributing questionnaires directly. The data analysis technique used in this research is PLS-SEM (Partial et al. Equation Modeling) analysis with the help of SmartPLS version 3.0 software.Findings:The results of this research show that (1) Auditor independence has a positive effect on the audit quality of the Badung Regency Government Inspectorate, (2) Auditor experience has a positive effect on the audit quality of the Badung Regency Government Inspectorate.Implication:(3) The auditor's professional ethics can moderate the influence of auditor independence on the audit quality of the Badung Regency Government Inspectorate, and (4) The auditor's professional ethics are not able to moderate the influence of the auditor's experience on the audit quality of the Badung Regency Government Inspectorate.